IMF Staff papers : Volume 29 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1982)
This study analyzes the circumstances under which monetary policy can be conducted to improve the stability of both monetary growth and exchange rates. For this purpose, the paper develops a portfolio balance model and tests its implications using parameter estimates for the United States and the United Kingdom. The principal finding is that there is a limited set of conditions in which stability of monetary growth and stability of exchange rates are consistent policy objectives. The two intervention rules compared here are stylized versions of rules that are commonly employed by central banks in countries with well-developed financial markets: control of the growth of the monetary base and control of a short-term interest rate. It is shown that a general rule is that when the supply function for money is more variable than the demand function, then monetary stability and exchange rate stability are likely to be operationally consistent targets.